Wasiat Wajibah Bagi Kerabat Yang Terhalang Mendapatkan Warisan (Sebuah Rechtsvinding) - Suratman Suratman; Sulasiyah Amini (Fakultas Hukum Universitas Islam Malang, 2022)
This paper was compiled with the aim of knowing the considerations of relatives who are prevented from getting an inheritance due to different religions through the mandatory will system and the position of the mandatory will in the perspective of Islamic law. The research method used is normative juridical. Based on the results of the study, it was concluded that consideration of relatives who were prevented from obtaining an inheritance due to different religions, still getting inheritance with a mandatory will system was carried out through the argumentum per analogium method. With a mandatory will, the Supreme Court has made a legal step and this is a rechtsvinding. Based on the perspective of Islamic law, the implementation of the mandatory will is in line with the understanding that Islam is a religion that has the aim of applying the principles of justice as stated in the Qur'an and Hadith.